Pengaruh Perpustakaan Perguruan Tinggi Keagamaan Negeri terhadap Preferensi Buku Bacaan Mahasiswa - Erland Cahyo Saputro; Farida Nur Hidayah; Triningsih Triningsih (Jurnal Pustaka Ilmiah, 2025)
The State Religious College Library plays a significant role in shaping students' reading material preferences. This study aims to explain the influence of the State Religious College Library on the reading book preferences of students at the Raden Mas Said State Islamic University of Surakarta, the Raden Wijaya State Buddhist College of Wonogiri, Central Java, and the I Gusti Bagus Sugriwa State Hindu University of Denpasar, Bali. This study uses a quantitative explanatory method by taking a sample of 83 students through accidental sampling techniques. Data collection using a literature study questionnaire and observation. As well as data analysis techniques using the help of statistical tools, SPSS IBM V25. The results of the study indicate that there is an influence between the State Religious College Library represented by the Raden Mas Said State Islamic University Library of Surakarta, the Raden Wijaya State Buddhist College of Wonogiri, and the I Gusti Bagus Sugriwa State Hindu University of Denpasar, Bali on students' reading book preferences with a significance value of 0.000 <0.005 and has an influence value of 24.2%. Reading materials that are often borrowed at each university are books on Islamic themes such as Fiqh Muamalah at UIN Raden Mas Said Surakarta, books on Buddhism such as the Philosophy of Buddhism at the Raden Wijaya State Buddhist College in Wonogiri, and books on Hinduism such as the Philosophy of Hinduism at the I Gusti Bagus Sugriwa State Hindu University in Bali.